Supported Palladium Catalysts for the Selective Hydrogenation of Furfural with Polymethylhydrosiloxane. - Medina Ruíz, M Esther; Maderuelo-Solera, Rocío; Jiménez-Gómez, Carmen Pilar; Moreno-Tost, Ramón; Malpartida-García, Irene; García-Sancho, Cristina; Cecilia-Buenestado, Juan Antonio; Len, Christophe; Maireles-Torres, Pedro Jesús (American Chemical Society, 2024)
A series of Pd-based catalysts supported on oxides with different acid−base properties has been prepared, characterized, and used for the valorization of furfural into value-added chemicals, with polymethylhydroxysiloxane (PMHS) as a reducing agent being an alternative to the use of hydrogen gas and alcohols as hydrogen donors. PMHS is a polymeric waste product of the silicone industry and is also recognized as a sustainable reductant for epoxide hydrosilylations and diastereoselective radical reduction in organic chemistry. Moreover, it is nontoxic, water/air insensitive, and soluble in most organic solvents due to its low viscosity. So, PMHS has been employed for the reduction of furfural in the presence of supported Pd catalysts. Although all catalysts tested are catalytically active, those supported on Al2O3 and SiO2 showed complete conversion after 30 min of reaction at 303 K, whereas 27.7% was attained using MgO as support.
ACS Sustainable Chemistry & Engineering
Keywords: Catálisis heterogénea; Biomasa; Ingeniería química; Polymethylhydrosiloxane; Furfural; Biomass; Palladium; Heterogeneous catalysis